A new method for the structural optimisation of a common type of square wing plate used in the wave glider. (3rd October 2019) - Zhao, Jian; Gao, Zhipeng; Hou, Yanyan; Hong, Xuewu; Liu, Haiqiang; Wang, Da; He, Yilong
ABSTRACT: The wave glider is widely used in marine engineering. As one of the most crucial components of the wave glider, the wing plate system significantly affects the utilisation efficiency of wave energy. The aim of this research is to optimise the structure of a kind of the square wing plate, which possesses a bad hydrodynamic performance. For the purpose, a new structural optimisation method was developed, in which the optimal sweepback angle and leading edge radius of square wing plate were calculated. Structural dynamic sensitivity analysis and matrix perturbation theory were combined to establish a proper guidance for structural modification, which could avoid blindness during structural modification. Then, dynamics characteristics of the optimised wing plate were investigated based on finite element analysis and experimental modal testing. Finally, the hydrodynamic performance of the optimised wing plate was evaluated. Results show that the newly proposed optimisation method is feasible and effective, and it also can be used for wing plates in other underwater vehicle applications.